2022
DOI: 10.14366/usg.20213
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of shear-wave elastography for the evaluation of varicocele in adolescents and young adults

Abstract: To compare the change of testicular stiffness during the Valsalva maneuver using shear-wave elastography (SWE) in adolescents and young adults with varicocele according to clinical severity and evaluate the role of SWE in the diagnosis of varicoceles.Methods: Patients undergoing testicular ultrasonography for diagnosis of varicocele or for follow-up after varicocelectomy from June 2016 to February 2017 were included in this study. 54 testicles of 27 consecutive patients (mean age, 15.9 years) were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…According to current literature, it is clear that age and BMI [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , varicocele grade [28] , [29] , [30] , [31] and testicular elasticity modulus [32] , [33] , [34] , [35] have a definite impact on male fertility and sperm quality. Interestingly, the multivariate logistic regression analysis showed that BMI had no predictive value for the improvement of sperm parameters after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to current literature, it is clear that age and BMI [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , varicocele grade [28] , [29] , [30] , [31] and testicular elasticity modulus [32] , [33] , [34] , [35] have a definite impact on male fertility and sperm quality. Interestingly, the multivariate logistic regression analysis showed that BMI had no predictive value for the improvement of sperm parameters after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ryu YJ noted no difference in the Emean SWE values during resting states but increased testicular stiffness during the Valsalva maneuver for grade II and III varicoceles [ 50 ].…”
Section: 2 Testiclementioning
confidence: 99%
“…As in previously conducted studies, automatically generated average stiffness values were used. [ 17 23 ] The average of the all 3 poles measurements was calculated. The results were recorded in units of kPa.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%